The Thirdspace Movement Model for Inclusion and Social Justice in Physical Education. Issue 4 (4th May 2023) - Haneishi, Kanae; Block, Betty; Zarco, Emilia Patricia; Prados-Megías, M. Esther; Johnson, Marcus
Abstract: This article introduces the concept of a new curricular model that addresses these issues through the body. The Thirdspace Movement Model can be integrated in K-12 Physical Education in coordination with other models. The Thirdspace Movement Model creates an environment where students practice movements and engage in critical discourse that address embodied identity. Through movements, the model fosters; 1) self-awareness which can lead to self-identity and self-acceptance, 2) embodied movement experiences that can lead to inner peace, 3) humanization, 4) acceptance of self and others, 5) reconciliation, 6) growth in connection with others, and 7) justice. The Thirdspace Movement Model can be integrated with existing PE units or introduced as a stand-alone unit. Self-awareness and listening to the messages the body sends begins the learning experience. Students then explore and express through developmental progression and movement patterns with self and others. The experience culminates with critical dialogue activities aimed at reflecting how bodily knowing and embedded memories influence one's movements and actions.